Single‐cell RNA sequencing for traumatic spinal cord injury. Issue 12 (14th November 2022) - Cao, Yuqi; Zhu, Shunxing; Yu, Bin; Yao, Chun
Abstract: Traumatic spinal cord injury (tSCI) is a severe injury of the central nervous system (CNS) with complicated pathological microenvironment that results in hemorrhage, inflammation, and scar formation. The microenvironment of the injured spinal cord comprises heterogeneous neurons, glial cells, inflammatory cells, and stroma‐related cells. Increasing evidence has indicated that the altered cellular and molecular microenvironment following tSCI is a key factor impeding functional recovery. Single‐cell RNA sequencing (scRNA‐seq) has provided deep insights into the dynamic cellular and molecular changes in the microenvironment by comprehensively characterizing the diversity of spinal cord cell types. Specifically, scRNA‐seq enables the exploration of the molecular mechanisms underlying tSCI by elucidating intercellular communication in spinal cord samples between normal and injury conditions at a single‐cell resolution. Here, we first described the pathological and physiological processes after tSCI and gave a brief introduction of the scRNA‐seq technology. We then focused on the recent scRNA‐seq researches in tSCI, which characterized diverse cell‐type populations and specific cell–cell interactions in tSCI. In addition, we also highlighted some potential directions for the research of scRNA‐seq in tSCI in the future.